(untitled) (Journal of Partial Differential Equations, 2021)
This article deals with an averaging principle for Caputo fractional stochastic differential equations with compensated Poisson random measure. The main contribution of this article is to impose some new averaging conditions to deal with the averaging principle for Caputo fractional stochastic differential equations. Under these conditions, the solution to a Caputo fractional stochastic differential system can be approximated by that of a corresponding averaging equation in the sense of mean square.